دور الجماعات المحلية في تنفيذ السياسة البيئية في الجزائر - بن عطاالله, محـمد الأمين; علقـمي, عبد اللطيف (جامعة الوادي university el-oued, 2017)
تطرقت الدراسة إلى دور الجماعات المحلية في تنفيذ السياسة البيئية في الجزائر والوقوف على حالة بلدية تقرت في هذا خلال الفترة الممتدة ما بين 2011 و2016، من خلال ذلك تم تناول الإستراتيجية الوطنية لحماية البيئة وتطور السياسة البيئية وأهم القوانين التي تمثل أداة للسياسة البيئية في الجزائر، كما أنه من خلال التطرق إلى مهام وصلاحيات الجماعات المحلية لحماية البيئة تم تقويم دور الجماعات المحلية في تنفيذ السياسة البيئية حيت تم استنتاج على أن صنع وتنفيذ السياسة العامة البيئية لا تتم في إطار تشاركي نتيجة هيمنة السلطة التنفيذية على وظائف الجماعات المحلية في وضع السياسات العامة المحلية، كما خلصت الدراسة إلى عدم قدرة الجماعات المحلية في زيادة فعالية تنفيذ السياسة البيئة لتحقيق متطلبات التنمية المستدامة نظرا لعدة اعتبارات من بينها النقائص الكبيرة التي تؤثر على أداء الجماعات المحلية مثل الكفاءات المتخصصة وعدم فهم للقوانين ومدى استقلالية الجماعات المحلية، لذلك يجب العمل من رفع مستوى أداء الجماعات المحلية في ممارسة صلاحياتها ووظائفها من خلال وجود منتخبين محليين ذو كفاءة في التسيير بالإضافة إلى دعم قواعد الشراكة في تسيير الشؤون العامة على المستوى المحلي .The study focused on the role of local communities in the implementation of the environmental policy in Algeria and the status of municipality in this period between 2011 and 2016. The national strategy for environmental protection and the development of environmental policy and the most important laws which represent an instrument of environmental policy in Algeria, That by addressing the functions and powers of local environmental groups, the role of local communities in the implementation of environmental policy has been assessed. It has been concluded that environmental policy-making and implementation are not carried out in a participatory framework, The study also found that local communities are unable to increase the effectiveness of environmental policy implementation to meet sustainable development requirements due to several factors, including significant shortcomings affecting the performance of local communities such as specialized competencies, lack of understanding of the laws and the autonomy of local communities, From raising the performance of local communities in the exercise of their powers and functions through the presence of local elected candidates with efficient management and support
مدكرة ماستر